The Florida Geographic Data Library: Lessons Learned and Workflows for Geospatial Data Management. Issue 1 (2nd January 2016) - Goodison, Crystal; Guillaume thomas, Alexis; Palmer, Sam
Abstract : The University of Florida GeoPlan Center has been organizing, standardizing, and distributing geospatial data since 1998 through the Florida Geographic Data Library (FGDL), a collection of Florida geospatial data from various agencies, as well as data developed in-house. With funding from the Florida Department of Transportation (FDOT), FGDL serves as a public distribution mechanism for hundreds of Florida geospatial data layers. Since 2004, FGDL layers have formed the data foundation for FDOT's interagency application known as efficient transportation decision making (ETDM), which facilitates the review and permitting process for proposed transportation projects. Data layers are standardized and inspected to ensure that the data are adequate for use in analysis and decision making. To efficiently manage the geospatial data and workflows, a quality assurance/quality control (QAQC) process and relational database schema was developed to track the standardization procedures, lineage, versioning, and archiving of the data layers. This article details the history of the Florida Geographic Data Library, challenges of managing a large geospatial data repository, development of a QAQC process and database schema, and lessons learned.